2015
DOI: 10.1007/s00424-015-1722-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen sensing in intestinal mucosal inflammation

Abstract: Hypoxia is a hallmark of chronically inflamed tissue. Hypoxia develops from vascular dysfunction and increased oxygen consumption by infiltrating leukocytes. With respect to inflammatory bowel disease (IBD), hypoxia is likely to be of particular importance: Impairment of the intestinal barrier during IBD allows anoxia from the lumen of the gut to spread to formerly normoxic tissue. In addition, disturbed perfusion of inflamed tissue and a higher oxygen demand of infiltrating immune cells lead to low oxygen lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…In contrast, PHD hydroxylation does not occur under hypoxia, which stabilizes HIF-α/β to activate hypoxia-responsive genes (33). FG-4592 is an oral inhibitor of HIF PHDs that stabilizes HIF-α/β and triggers a hypoxia transcriptional program under normoxic conditions (35)(36)(37). Transcriptional profiling indicated that Ae.…”
Section: Cytochrome Bd Oxidase-dependent Respiration Reduces Gut Oxygenmentioning
confidence: 99%
“…In contrast, PHD hydroxylation does not occur under hypoxia, which stabilizes HIF-α/β to activate hypoxia-responsive genes (33). FG-4592 is an oral inhibitor of HIF PHDs that stabilizes HIF-α/β and triggers a hypoxia transcriptional program under normoxic conditions (35)(36)(37). Transcriptional profiling indicated that Ae.…”
Section: Cytochrome Bd Oxidase-dependent Respiration Reduces Gut Oxygenmentioning
confidence: 99%
“…In addition, infiltrating neutrophils at sites of inflammation contribute to hypoxia, as these cells require high levels of oxygen to support the oxidative burst that is used as an endogenous antimicrobial strategy (8,9). Reduced oxygenation of inflamed tissues is of particular relevance in chronic inflammatory diseases of the intestine, such as inflammatory bowel disease, where the development of thrombosis, fibrosis, and associated vascular dysfunction often leads to diminished tissue perfusion (10,11). Therefore, hypoxia is a common feature of the microenvironment of chronically inflamed tissues.…”
Section: The Relationship Between Hypoxia and Inflammationmentioning
confidence: 99%
“…Another cause of hypoxia during inflammation is disrupted oxygen delivery. This is particularly the case in chronic inflammation where the combination of prolonged inflammatory activity and associated fibrosis and thrombosis results in diminished blood (and consequently oxygen) supply to the site of inflammation [11]. Therefore, a combination of increased oxygen consumption by inflamed resident cells and infiltrating immune cells along with a disrupted blood supply due to vascular dysfunction contributes to tissue hypoxia during chronic inflammation ( Figure 1).…”
Section: Hypoxia In Inflammationmentioning
confidence: 99%